Формування інтродукційних популяцій субтропічних плодових культур у Хорольському ботанічному саду - Красовський, Володимир; Кrasovsky, Volodymyr (Східноєвропейський національний університет імені Лесі Українки, 2017)
Зазначено, що формування інтродукційних популяцій Asimina triloba (L.) Dunal, Punica granatum L., Zizyphus jujuba Mill., Ficus carica L., Amygdalus communis L., Diospyros virginiana L. у лісостеповій зоні України дає змогу створити біотичні системи субтропічних плодових культур, які характеризуються певною екологічною й генетичною структурою цих видів, де реалізуються гібридизаційні процеси. It was shown, forming of artificial introduction populations Asimina triloba (L.) Dunal, Punica granatum L., Zizyphus jujuba Mill., Ficus carica L., Amygdalus communis L., Diospyros virginiana L. in Khorol botanical garden allows to create biotical systems of subtropical fruit crops, characterizing some ecological and genetic structure of this species where hybrid process take place. Taking account the size of botanic and geographic area of subtropical fruit crops garden, it was defined the sample quantity of every investigation species, which are A. triloba – 70 things, P. granatum – 6 things, Z. jujuba – 50 things, F. carica – 8 things, A. communis – 4 things, D. virginiana – 26 things. Growing of crops as local groups is one of the important activity in optimization of introduction process. The created collection is real genetic bank of subtropical fruit crops in the forest steppe zone of Ukraine and the source material for selection.
Forming of Introduction Populations of the Subtropical Fruit Crops in Khorol Botanical Garden.
Keywords: Лісостеп України; гібридизація; локальна популяція; інтродукція; субтропічні плодові культури; Forest steppe of Ukraine; hybridizing; local population; introduction; subtropical fruit crops